Three-dimensional craniofacial surface measurement: linear distance, angle and area computation - Chuan, Shuen Chuan; Setan, Halim; Majid, Zulkepli (2006)
Accurate and precise measurement of three-dimensional surface in terms of linear distance, area occupied and angles between surfaces have become key criteria particularly in reconstruction of craniofacial appearance where the main purpose is to restore a distorted or damage facial area according to surgeons and patients requirements from aesthetic point of view. This paper describes three techniques used in three-dimensional surface measurement using practical mathematical computation together with the usability requirements descriptions. These techniques are described in terms of its purposes of usage, implementation process and mathematical calculation. We summarized in the end that all the above discussed approaches are practically useful in three-dimensional surface measurement and computation.